The Effect of Service Quality and Zocco Coffee Atmosphere Quality on Customer Satisfaction - Tania Leony Tantono; Christina Sudyasjayanti (Universitas Ciputra Surabaya, 2021)
This research was conducted to determine the effect of Service Quality and Atmosphere Quality at Zocco Coffee's Customer Satisfaction. This research is a quantitative research, sampling is done by non-probability sampling method. The analytical method used is multiple linear regression analysis. The source of data in this study is primary data obtained by distributing 150 questionnaires to respondents who are at least 15 years old with the criteria of having visited Zocco Coffee twice in the last three months and there are 140 questionnaires that are worthy of analysis. Customer satisfaction is an absolute thing that must be considered by the company. If the company's performance can meet expectations, the customer will be satisfied, and vice versa. Service Quality in internet cafe objects can be measured by several indicators, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy. Atmosphere Quality is the physical quality that is presented such as music, room temperature, cleanliness and employee appearance that affects the emotional response of customers and has a dominant effect on customer satisfaction. The results of hypothesis testing indicate that service quality has a significant effect on customer satisfaction and atmosphere quality has a significant and dominant effect on customer satisfaction at Zocco Coffee.